Mitochondrial dysfunction: A notable contributor to the progression of Alzheimer's and Parkinson's disease. Issue 3 (March 2023) - Olagunju, Abolaji Samson; Ahammad, Foysal; Alagbe, Abiola Adeyanju; Otenaike, Titilayomi Ayomide; Teibo, John Oluwafemi; Mohammad, Farhan; Alsaiari, Ahad Amer; Omotoso, Olabode; Talukder, Md Enamul Kabir
Abstract: Mitochondrial dysfunction remains a pivotal mechanism in manifold neurodegenerative diseases. Mitochondrial homeostasis within the cell is an essential aspect of cell biology. Mitochondria, the power-generating organelle of the cell, have a dominant role in several processes associated with genomic integrity and cellular equilibrium. They are involved in maintaining optimal cell functioning and ensuring guidance against possible DNA damage, which could lead to mutations and the onset of diseases. Conversely, system perturbations, which could be due to environmental factors or senescence, induce changes in the physiological balance and result in mitochondrial function impairment. As a result, we present a general overview of the pathological pathways involved in Alzheimer's and Parkinson's diseases caused by changes in mitochondrial homeostasis. The focal point of this review is on mitochondrial dysfunction being a significant condition in the onset of neuronal disintegration. We explain the pathways associated with the dysfunction of the mitochondria, which are common among the most recurring neurodegenerative diseases, including Alzheimer's and Parkinson's disease. Are mitochondrial dysfunctions an early event in the progression of neuropathological processes? We discovered that mtDNA mutation is a major contributor to the metabolic pathology of most neurological disorders, causing changes in genes important for physiological homeostasis. As a result, genetic changes in presenilin, Amyloid-, ABAD, DJ-1, PINK-1, PARKIN, alpha-synuclein, and other important controlling genes occur. Therefore, we suggest possible therapeutic solutions. Graphical abstract: Image 1